THE HUNTER OF MAN - Malone, E.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
The origins of sniping - the ability to kill one’s enemy at a range far exceeding that of ordinary military rifles - may be traced at least as far back as 1755, in which year the British Government, licking their wounds after an inglorious defeat on the banks of the Ohio River by a combined French and Red Indian force, raised from among the American settlers a unique corps of trained marksmen, whose arms, dress and mobility approximated those of their enemies. This corps d’elite, whose birthday is given as Christmas Day 1755, was orignally named the 2nd Regiment, the title being subsequently altered to the 60th ’Royal Americans’.